2012
DOI: 10.1182/blood-2012-03-415349
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of ribosomal protein L22 promotes transformation by induction of the stemness factor, Lin28B

Abstract: Ribosomal protein (RP) mutations in diseases such as 5q؊ syndrome both disrupt hematopoiesis and increase the risk of developing hematologic malignancy. However, the mechanism by which RP mutations increase cancer risk has remained an important unanswered question. We show here that monoallelic, germline inactivation of the ribosomal protein L22 (Rpl22) predisposes T-lineage progenitors to transformation. Indeed, RPL22 was found to be inactivated in ϳ 10% of human T-acute lymphoblastic leukemias. Moreover, mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
162
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(167 citation statements)
references
References 50 publications
(88 reference statements)
3
162
0
2
Order By: Relevance
“…Mutations within ribosomal genes have been identified in various syndromes or inherited conditions, mainly affecting the erythroid lineage (eg, DiamondBlackfan anemia); however, mutations within RPL5, RPL10, and RPL22 were recently reported in T-cell acute lymphoblastic leukemia. 33,34 Prompted by our findings, we screened a larger number of cases to not only obtain deeper insights into the frequency of RPS15 in CLL, but also, for the first time, to investigate their association with clinicobiological features and their impact on disease outcome. In the adverse prognostic patient group (mainly comprising U-CLL), we found that 6% of patients carried RPS15 mutations, of which one-third (11/36) also harbored TP53 aberrations; on the other hand, no RPS15 mutations were detected in the more favorable prognostic, IGHV-mutated CLL.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations within ribosomal genes have been identified in various syndromes or inherited conditions, mainly affecting the erythroid lineage (eg, DiamondBlackfan anemia); however, mutations within RPL5, RPL10, and RPL22 were recently reported in T-cell acute lymphoblastic leukemia. 33,34 Prompted by our findings, we screened a larger number of cases to not only obtain deeper insights into the frequency of RPS15 in CLL, but also, for the first time, to investigate their association with clinicobiological features and their impact on disease outcome. In the adverse prognostic patient group (mainly comprising U-CLL), we found that 6% of patients carried RPS15 mutations, of which one-third (11/36) also harbored TP53 aberrations; on the other hand, no RPS15 mutations were detected in the more favorable prognostic, IGHV-mutated CLL.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is indirect evidence of an interaction including that both ATP5C1 and RelA were reported to interact with mediator complex subunit 15 (MED15/ARC105), an RNA polymerase II transcription cofactor activity involved in transcription initiation. These interactions were detected by yeast two-hybrid and pulldown assays, respectively, in Stelzl et al (64) and Näär et al (65). In a recent study of the transcriptional response to relaxation training, ATP5C1 was one of the top up-regulated critical molecule, and served as a hub in the interactive network of the relaxation response-affected pathway.…”
Section: Triplets Predicted Using the Candidate Nf-b/rela Modulators mentioning
confidence: 99%
“…LIN28A or LIN28B expression is associated with chronic myelogenous leukemia (CML), hepatocellular carcinoma, neuroblastoma, and cancers of the lung, breast, ovary, cervix, colon, and rectum King et al 2011a,b;Diskin et al 2012;Molenaar et al 2012). In addition, LIN28B expression is elevated or ectopically expressed in Wilm's tumors ), prostate cancer (Iliopoulos et al 2009), and T-acute lymphoblastic leukemias (T-ALLs) (Rao et al 2012). In cell lines, LIN28A or LIN28B are necessary and sufficient for promoting proliferation, soft agar colony formation, migration, invasion, and metastasis in xenograft mouse models (Iliopoulos et al 2009;Viswanathan et al 2009;King et al 2011b).…”
mentioning
confidence: 99%